2022
DOI: 10.1002/ece3.9139
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale nest‐site selection of ducks in the western boreal forest of Alberta

Abstract: There is limited data regarding the nesting ecology of boreal ducks and their response to industrial development, despite this region being an important North American breeding area. We investigated how landcover and oil and gas development affect third‐order nest‐site selection of boreal ducks. We located duck nests in Alberta's western boreal forest between 2016 and 2018. We used multiscale analysis to identify how scale affects the selection of a resource using generalized linear mixed‐effects models and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 91 publications
5
29
2
Order By: Relevance
“…Marsh was a grouped variable (Table 1), which characterized the transition zone between shrub swamp, graminoid fen, open water areas, and forests (Smith et al 2007). Female mallards selected marsh habitat across scales and these results were consistent with Dyson (2020) who demonstrated boreal ducks selected nest sites with greater marsh cover within 300 m of the nest. This is likely attributed to the foraging, resting, and nesting opportunities that marshes provide for ducks (Pearse et al 2012, Beatty et al 2014 b , Stafford et al 2016).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Marsh was a grouped variable (Table 1), which characterized the transition zone between shrub swamp, graminoid fen, open water areas, and forests (Smith et al 2007). Female mallards selected marsh habitat across scales and these results were consistent with Dyson (2020) who demonstrated boreal ducks selected nest sites with greater marsh cover within 300 m of the nest. This is likely attributed to the foraging, resting, and nesting opportunities that marshes provide for ducks (Pearse et al 2012, Beatty et al 2014 b , Stafford et al 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Selection for shrub swamps is consistent with the limited available research; however, the avoidance of swamps was surprising given previous research that suggested ducks settling in the eastern boreal forest prefer wetlands with swamp peripheries over shrub swamp peripheries (Lemelin et al 2010). In terms of nest site selection in the region, nesting ducks exhibited a scale‐dependent response and avoided swamps at coarse scales, but selected swamps at fine spatial scales (Dyson et al 2022). We suspect that shrub swamps provided forage opportunities (Straub et al 2012) and dense vegetative cover for concealment from predators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations